2023
DOI: 10.1039/d2dt03238d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced film quality of PbS QD solid by eliminating the oxide traps through an in situ surface etching and passivation

Abstract: PbS QDs received considerable interests in optoelectronics. However, their high susceptibility to oxidation results in the production of Pb oxides on PbS, which can induce sub-bandgap traps in PbS QDs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Compared to the pristine Co@N‐C, we found that the immobilization of HMII leads to the appearance of additional new peaks at 619.0 and 630.6 eV, which is assigned to I 3 d signal (Figure 2A). [ 17 ] This result together with the elemental mapping analyses (Figure S1, Supporting Information) confirmed the binding of HMII on Co@N‐C. Figure 2B shows the high‐resolution I 3 d spectrum for the HMII immobilized sample with the peak positions indicating the different species identified by spectrum deconvolution.…”
Section: Resultsmentioning
confidence: 55%
“…Compared to the pristine Co@N‐C, we found that the immobilization of HMII leads to the appearance of additional new peaks at 619.0 and 630.6 eV, which is assigned to I 3 d signal (Figure 2A). [ 17 ] This result together with the elemental mapping analyses (Figure S1, Supporting Information) confirmed the binding of HMII on Co@N‐C. Figure 2B shows the high‐resolution I 3 d spectrum for the HMII immobilized sample with the peak positions indicating the different species identified by spectrum deconvolution.…”
Section: Resultsmentioning
confidence: 55%